Hypoglycemic and antihyperglycemic effect of different extracts of acacia arabica lamk bark in normal and alloxan induced diabetic rats - Mohammad Yasir,; Prateek Jain,; Debajyoti,; M.D.Kharya, (International Journal of Phytomedicine, 2010)
Acacia arabica commonly known as babool are used in traditional Indian medicine for treatment of diabetes mellitus. The hypoglycemic effect of aqueous extract (hot and cold water) and hydroalcoholic extract of Acacia arabica was investigated. Oral administration of cold water extract of Acacia arabica bark to diabetic and normal rats at a dose of 400 mg/kg body weight resulted in significant reduction of blood glucose, cholesterol and triglycerides. Phytochemical investigations found that phenolic compounds are presents in Acacia arabica extracts. The cold water extract of Acacia arabica was found to reduce blood glucose level to its normal level with in seven days. Histological studies of the β- cells show its action on pancreas.